Planning for the Preservation of Biodiversity and Environmental Assets in Support of Sustainable Planning in Urban Areas, Case Study: Batu Licin City, Tanah Bumbu Regency, South Kalimantan - Kalsuma, Dharma; Simarmata, Hendricus Andy (Smart City, 2023)
Planning for preserving biodiversity and environmental assets in urban areas is crucial in supporting sustainable planning. This study aims to design a strategy for preserving biodiversity and environmental assets in Batu Licin, Tanah Bumbu Regency, South Kalimantan, to support sustainable urban planning. The method used is field observation and literature study. The results showed that the Batu Licin area has a relatively high potential for biodiversity and environmental assets. However, along with the growth of the Batu Licin urban area in the future, it will undoubtedly be a source of pressure on biodiversity. Several strategies can be implemented to overcome this, including mainstreaming biodiversity in sectoral planning, strengthening the knowledge base on conservation, management, and use of biodiversity assets, increasing awareness and appreciation for environmental services and biodiversity, implementing area protection and restoration policies for high- value ecosystems and biodiversity assets, and mainstreaming climate change adaptation and mitigation. This strategy can become a reference for policymakers in planning sustainable development in the urban area of Batu Licin and other regions in Indonesia.